Human Accessibility Modelling Applied to Protected Areas Management - Esteves, Carolina Franco [UNESP]; de Barros Ferraz, Silvio Frosini; Micchi de Barros Ferraz, Katia Maria Paschoaletto; Galetti, Mauro [UNESP]; Theobald, David Martin (Assoc Brasileira Ciência Ecologica E Conservacao, 2011)
Natural protected areas in tropical regions are considered important refuges for flora and fauna, and the only remaining habitat for many species. However, these areas still suffer from numerous human impacts, whether by illegal hunting, logging or tourism. Mapping areas of greater human access and its potential effect to wildlife should be considered as strategy for management in protected areas. This study aimed to generate a human accessibility map for the Anchieta Island, for purposes of zoning and management. We evaluated the impact of human presence (tourism) on the occurrence of wildlife at Anchieta Island by using the concept of human accessibility. Accessibility model was correlated with estimated travel-time using Pearson's Correlation and showed significant positive relationship (r = 0.714) between accessibility model and travel time observed in the field. Thus, the accessibility methodology can be a valuable tool to analyze human impacts on wildlife through hunting and logging in protected areas.
Keywords: Tourism; Cost-Distance; Anchieta Island State Park; Accessibility; Zoning